Neurobiological signatures associated with alcohol and drug use in the human adolescent brain. (November 2016) - Silveri, Marisa M.; Dager, Alecia D.; Cohen-Gilbert, Julia E.; Sneider, Jennifer T.
Highlights: Studies described point towards neurotoxic effects of alcohol and drugs. Most published alteration in substance-using adolescents is in the frontal lobe. Brain effects of substance use evident among relatively moderate users. Difficult to parse substance-specific brain abnormalities given co-use. Priority to close gap between neuroscience and practitioners treating adolescents. Abstract: Magnetic resonance (MR) techniques provide opportunities to non-invasively characterize neurobiological milestones of adolescent brain development. Juxtaposed to the critical finalization of brain development is initiation of alcohol and substance use, and increased frequency and quantity of use, patterns that can lead to abuse and addiction. This review provides a comprehensive overview of existing MR studies of adolescent alcohol and drug users. The most common alterations reported across substance used and MR modalities are in the frontal lobe (63% of published studies). This is not surprising, given that this is the last region to reach neurobiological adulthood. Comparatively, evidence is less consistent regarding alterations in regions that mature earlier (e.g., amygdala, hippocampus), however newer techniques now permit investigations beyond regional approaches that are uncovering network-level vulnerabilities. Regardless of whether neurobiological signatures exist prior to the initiation of use, this body of work provides important direction for ongoing prospective investigations of adolescent brain development, and the significant impact of alcohol and substance use on the brain during the second decade of life.